2011
DOI: 10.4236/oje.2011.12005
|View full text |Cite
|
Sign up to set email alerts
|

Impact profenophos (pesticide) on infectivity of <i>Biomphalaria alexandrina</i> snails with <i>schistosoma mansoni</i> miracidiaand on their physiological parameters

Abstract: Profenophos is an organophosphorus pesticide which are used effectively against cotton insects and mites.The present work was carried out to evaluate the molluscicidal activity of pesticides (Profenophos) against Biomphalaria alexandrina snails. Also, the effect of sublethal concentrations of pesticide on the infection of B. alexandrina with Schistosoma mansoni and some enzymes of energy metabolism were studied. The results showed that the infection of B. alexandrina with schistosoma mansoni was greatly reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…According to Tunholi et al (2011), the elevation of AST, ALT and ALP activities correlated with alteration in phospholipid metabolism and the high energy demand of the snail. Also, Mohamed (2011) explained the elevation of ALP level in the haemolymph of B. alexandrina snails due to the destruction of internal snail cells.…”
Section: Discussionmentioning
confidence: 99%
“…According to Tunholi et al (2011), the elevation of AST, ALT and ALP activities correlated with alteration in phospholipid metabolism and the high energy demand of the snail. Also, Mohamed (2011) explained the elevation of ALP level in the haemolymph of B. alexandrina snails due to the destruction of internal snail cells.…”
Section: Discussionmentioning
confidence: 99%
“…Bislimi et al (2013) recorded a significant increase of transaminases activity and catalase in the garden snail specimens (Helix pomatia L) which were collected from polluted area compared to control. Mohamed (2011) indicated that there are significant elevations in the level of ALP, after using of pesticides (Profenophos) against B. alexandrina, which can be explained by the destruction of internal snail cells. Meanwhile, in fish, these results agree with Zaghloul et al (2008), Tayel et al (2014), El-Khayat et al (2016) and Ismail et al (2017) who reported highly significant increase in the activities of AST, ALT and ALP in serum of O. niloticus in fish collected from lakes El-Burullus, Manzala and from highly polluted unlined sites at Giza and El-Beharia canals.…”
Section: Discussionmentioning
confidence: 99%
“…To date, despite the fact that many studies having documented the effects of pesticides on aquatic invertebrate and vertebrate fauna, none of these studies have assessed the effect of pesticides on the predator–prey interaction of Schistosoma host snails and their fish predators. However, studies specifically looking at the effects of pesticides on host snails have mainly focused on organophosphate pesticides, including the insecticides profenophos and chlorpyrifos, as studied by Hasheesh and Mohamed ( 2011 ) and Mohamed ( 2011 ), and these were found to have molluscicidal effects. Ibrahim et al ( 1992 ) observed decreased egg production and egg hatchability at sublethal concentrations and mortality at greater concentrations of chlorpyrifos by Biomphalaria alexandrina .…”
mentioning
confidence: 99%